Hydrophobic zeolite modification for in situ peroxide formation in methane oxidation to methanol - Jin, Zhu; Wang, Liang; Zuidema, Erik; Mondal, Kartick; Zhang, Ming; Zhang, Jian; Wang, Chengtao; Meng, Xiangju; Yang, Hengquan; Mesters, Carl; Xiao, Feng-Shou (Science (American Association for the Advancement of Science), 2020)
Selective partial oxidation of methane to methanol suffers from low efficiency. Here, we report a heterogeneous catalyst system for enhanced methanol productivity in methane oxidation by in situ generated hydrogen peroxide at mild temperature (70°C). The catalyst was synthesized by fixation of AuPd alloy nanoparticles within aluminosilicate zeolite crystals, followed by modification of the external surface of the zeolite with organosilanes. The silanes appear to allow diffusion of hydrogen, oxygen, and methane to the catalyst active sites, while confining the generated peroxide there to enhance its reaction probability. At 17.3% conversion of methane, methanol selectivity reached 92%, corresponding to methanol productivity up to 91.6 millimoles per gram of AuPd per hour.